The Analysis of Error Sources and Quality Assessment for Multibeam Sounding Products - Huang, Chenhu; Bian, Gang; Lu, Xiuping; Wang, Meina; Huang, Xianyuan; Wang, Keping (The International Hydrographic Review, 2017)
The use of multibeam sounding systems for bathymetric surveys requires an understanding of the gross errors and deviations caused by the dynamic marine environment and the instrumentation in use. This paper discusses these errors and the quality inspection specifications and processes applied to multibeam system measurements. The quality control plans covering the multibeam sounding data collection and stages of processing including pre-production, data evaluation, checking and final acceptance are then identified.